Abacavir use and cardiovascular disease events: a meta-analysis of published and unpublished data - Cruciani, Mario; Zanichelli, Veronica; Serpelloni, Giovanni; Bosco, Oliviero; Malena, Marina; Mazzi, Romualdo; Mengoli, Carlo; Parisi, Saverio G; Moyle, Graeme (AIDS (London), 2011)
The use of abacavir (ABC) has been associated with an increased risk of cardiovascular disease in some cohort studies. However, no excess risk of myocardial infarction (MI) with ABC therapy has been observed in individual randomized clinical trials (RCTs) and in the aggregated clinical trials database maintained by the manufacturer of ABC. To combine all the evidence from RCTs by means of meta-analysis to estimate the effect of combined antiretroviral therapy (cART) containing ABC on MI and overall major cardiovascular events (CVEs). Primary outcomes included MI, CVE, adverse events requiring discontinuation of treatment, and overall mortality. We used a conventional Mantel-Haenszel method, with risk ratio and 95% confidence intervals (CIs) or, in the presence of heterogeneity, a random-effect model. Data were from 28 primary RCTs (9233 participants) comparing ABC-containing cART (4376 participants) to other regimens not containing ABC (4857 controls). MI data were available from 18 trials (31 episodes in 7054 patients) and CVE data from 20 trials (79 episodes in 7899 patients). Compared to the controls, ABC use did not increase significantly the occurrence of MI (risk ratio 0.73, 95% CI 0.39-1.35; P = 0.31), CVE (risk ratio 0.95, 95% CI 0.62-1.44; P = 0.80), overall mortality (risk ratio 1.20, 95% CI 0.63-2.27; P = 0.58), and adverse events requiring discontinuation of treatment (risk ratio 0.82, 95% CI 0.67-1.00; P = 0.05). This meta-analysis of RCTs does not support the hypothesis that ABC-containing cART regimens carry a greater risk of MI or major cardiovascular events relative to comparator cART.